Expanded carbon layer reinforced water-based fireproof coating as well as preparation method and application thereof

By modifying titanium dioxide to enhance the strength of the expanded carbon layer and inhibit smoke release, the problem of easy damage to the carbon layer of traditional fire-retardant coatings at high temperatures is solved, and efficient fire protection and smoke suppression effects are achieved.

CN120737696AActive Publication Date: 2025-10-03TIANJIN FIRE SCI & TECH RES INST OF MEM

Patent Information

Application Number
CN202511231821.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-01
Publication Date
2025-10-03
Estimated Expiration
2045-09-01

AI Technical Summary

Technical Problem

The carbon layer of existing intumescent fire-retardant coatings is easily damaged and falls off at high temperatures, making it difficult to balance the intumescent performance and the strength of the carbon layer. In addition, traditional coatings are difficult to suppress smoke release.

Method used

Modified titanium dioxide is used as a flame retardant, which is modified through boron/silicon compounds and phytic acid to form a composite synergistic flame retardant element, enhance the strength of the carbon layer and inhibit smoke release, and improve compatibility with the water-based resin matrix.

Benefits of technology

It maintains the structural integrity of the expanded carbon layer at high temperatures, effectively inhibits smoke release, and improves fire protection effects. It is suitable for fire-retardant coatings for steel structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120737696A_ABST
    Figure CN120737696A_ABST
Patent Text Reader

Abstract

The invention provides an expanded carbon layer reinforced water-based fireproof coating as well as a preparation method and application thereof, and belongs to the technical field of fireproof coatings. By combining the high dispersibility and high-temperature-resistant stability of modified titanium dioxide, the gas-phase / condensed-phase flame-retardant effect of phosphorus-containing phytic acid and the ceramifiable ability of boron / silicon compounds, the high-performance and environment-friendly expanded carbon layer reinforced water-based fireproof coating is developed on the basis of a traditional'ammonium polyphosphate-pentaerythritol-melamine 'expanded flame-retardant system. A coating sample prepared from the water-based fireproof coating can form a high-quality expanded carbon layer during combustion, is high in density, still keeps a complete structure under severe conditions such as high temperature and spray combustion, can provide long-term stable fireproof protection for a base material, can effectively inhibit release of combustible gas and flue gas particles, and improves the practical application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fire retardant coatings, and in particular to an expanded carbon layer reinforced water-based fire retardant coating, a preparation method thereof, and applications thereof. Background Art

[0002] Steel structures are one of the most common types of building support structures, offering advantages such as high strength, light weight, strong deformation resistance, and a wide range of applications. However, steel structures have an inherent disadvantage: they are not resistant to high temperatures. Their mechanical strength decreases rapidly with increasing temperature. In a fire, the load-bearing capacity of bare steel decreases by 40%-45% within 10 minutes, leading to collapse. Therefore, research on the fire protection of steel structures is necessary to improve the fire resistance of buildings and safeguard the lives and property of the public.

[0003] Fire-retardant coatings for steel structures can effectively slow heat transfer, inhibit fire spread, and reduce fire severity, buying valuable time for escape and rescue efforts. Given the current improvements in environmental regulations and the implementation of low-VOC emission standards, water-based intumescent fire-retardant coatings have garnered widespread attention. Using water as a dispersion medium, they consume less energy and significantly reduce hazards to humans and the environment during production and construction. Currently, the traditional intumescent flame-retardant system (PCN) consisting of ammonium polyphosphate (AMP)-pentaerythritol-melamine (MPP) is still considered to offer a good synergistic flame-retardant effect. However, with the rapid development of new materials and new business models, the fire risk and fire loads faced by buildings are increasing. Traditional intumescent fire-retardant coatings can suffer from char breakage and detachment under high-intensity heat flux or flame impact, compromising their fire-retardant effectiveness. Therefore, further enhancement of the fire protection capabilities of fire-retardant coatings is urgently needed.

[0004] The density and integrity of the expanded carbon layer directly impact its fire resistance. Numerous researchers, both domestically and internationally, have conducted in-depth research on improving the strength and stability of the expanded carbon layer in fire-retardant coatings. The simplest method is to add inorganic fillers (such as zinc borate, montmorillonite, aluminum hydroxide, silica, and titanium dioxide), which can effectively improve the thermal stability and integrity of the expanded carbon layer. However, to achieve better fire retardancy, the amount of refractory filler often needs to be increased. Due to the differences in surface / interface properties between inorganic powder fillers and the resin matrix, excessive amounts can reduce their dispersibility, negatively impacting the overall performance of the coating. Generally, surface modification can be used to improve the compatibility of inorganic fillers with the matrix resin. For example, the introduction of silane coupling agents can improve the interfacial properties of the material through chemical bonding. Chinese invention patent CN 119931433 A utilizes nano-titanium dioxide modified with a silane coupling agent, combined with alkali-treated glass fiber and acid-treated expandable graphite as reinforcing fillers in fire-retardant coatings. The resulting composite exhibits excellent carbon skeleton strength after ablation. However, this method involves modifying multiple materials, resulting in a complex process and hindering its practical application. In recent years, researchers have used the ceramicization reaction of intumescent fire-retardant coatings to improve the strength of the char layer. For example, Chinese invention patent CN 119463563 B utilizes glass powders with different melting temperatures as ceramic bodies so that the coating can form a gradient ceramic expansion layer during a fire, providing long-term, stable thermal protection for the substrate. However, this method faces the problem of compatibility between the inorganic powder and the substrate, which affects the overall performance of the coating.

[0005] Furthermore, it is worth noting that the release of toxic smoke in fires is a key factor in fatalities. Conventional intumescent fire retardant coatings struggle to suppress smoke, allowing it to spread easily. Therefore, it is necessary to develop a new technical solution for intumescent char-layer-reinforced fire retardant coatings to address the challenges of existing fire retardant coatings in terms of smoke release and the difficulty in balancing intumescent performance with char strength. Summary of the Invention

[0006] The purpose of the present invention is to provide an expanded carbon layer reinforced water-based fire-retardant coating and its preparation method and application. The expanded carbon layer reinforced water-based fire-retardant coating has good bonding strength, and its expanded carbon layer structure remains intact under harsh conditions such as high temperature and spraying. It can effectively suppress the release of smoke and solve the problem in the existing technology that it is difficult to balance the expansion performance and carbon layer strength of the fire-retardant coating.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides an intumescent carbon layer reinforced water-based fire retardant coating, which comprises the following preparation raw materials, based on the total mass fraction of the intumescent carbon layer reinforced water-based fire retardant coating being 100%: Film-forming substance 18~30%, flame retardant 45~60%, modified titanium dioxide 3.5~12%, additive 1~5%, water 13~25%; The preparation method of the modified titanium dioxide comprises the following steps: Mixing titanium dioxide, a first dispersant, a boron compound, a silicon compound, and an amino compound, adjusting the pH value to 3-4, and performing a first modification to obtain boron / silicon modified titanium dioxide; the amino compound is γ-aminopropyltriethoxysilane; The boron / silicon modified titanium dioxide is mixed with a second dispersant and a phytic acid solution to perform a second modification to obtain modified titanium dioxide.

[0008] Preferably, the boron compound includes one or more of trimethoxyboron, boric acid and trimethyl borate; The silicon compound includes one or more of ethyl orthosilicate, vinyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane and tetramethyl orthosilicate; The mass ratio of the titanium dioxide, the boron compound, the silicon compound and the amino compound is 8-10:1.25-2.5:0.5-1.5:1-3; The temperature of the first modification is 60-90 ° C, and the time is 5-7 h.

[0009] Preferably, the mass ratio of the boron / silicon modified titanium dioxide to the phytic acid solution is 2.5-5:1; The mass concentration of the phytic acid solution is 70%; The temperature of the second modification is 60-90 ° C, and the time is 3-5 h.

[0010] Preferably, the film-forming substance includes at least one of a water-based epoxy resin, a water-based acrylic resin, a water-based polyurethane resin, a water-based silicone resin, and a water-based alkyd resin.

[0011] Preferably, when the film-forming substance is a water-based epoxy resin, the film-forming substance further comprises a curing agent; and the mass ratio of the water-based epoxy resin to the curing agent is 10-20:1.

[0012] Preferably, the flame retardant comprises ammonium polyphosphate, pentaerythritol and melamine; the mass ratio of the ammonium polyphosphate, pentaerythritol and melamine is 2.67-3.25:1-1.5:1.25-1.75.

[0013] Preferably, the auxiliary agent includes at least one of a dispersant, a thickener, a wetting agent, a defoaming agent and an antibacterial agent.

[0014] Preferably, the dispersant includes sodium polyacrylate; the thickener includes a polyurethane thickener; the wetting agent includes a non-ionic wetting agent; the defoaming agent includes a silicone defoaming agent; and the antibacterial agent includes a Kathon antibacterial agent.

[0015] The present invention provides a method for preparing the expanded carbon layer reinforced water-based fire retardant coating described in the above technical solution, comprising the following steps: The film-forming material is dispersed in water, and a flame retardant, modified titanium dioxide and an auxiliary agent are added to obtain an expanded carbon layer reinforced water-based fire retardant coating.

[0016] The present invention provides the use of the expanded carbon layer reinforced water-based fire retardant coating described in the above technical solution or the expanded carbon layer reinforced water-based fire retardant coating prepared by the preparation method described in the above technical solution in steel structure fire retardant coating.

[0017] This invention provides an intumescent charcoal-reinforced water-based fire-retardant coating. Titanium dioxide is modified by grafting boron / silicon compounds and phytic acid to produce an organically modified titanium dioxide containing a composite synergistic flame-retardant element (phosphorus / boron / silicon). Not only is the titanium dioxide modified with boron / silicon ceramic precursors, but the introduced organic components of siloxane and phytic acid maintain good compatibility with the resin emulsion, thereby improving its dispersibility in the fire-retardant coating. This invention combines the high dispersibility and high-temperature stability of the modified titanium dioxide, the vapor / condensed-phase flame retardancy of the phosphorus-containing phytic acid, and the ceramicization ability of the boron / silicon compounds, based on the traditional "ammonium polyphosphate-pentaerythritol-melamine" intumescent flame-retardant system, to develop a high-performance, environmentally friendly intumescent charcoal-reinforced water-based fire-retardant coating. The coating samples prepared using this water-based fire-retardant coating can form a high-quality expanded carbon layer with high density during combustion. Its structure remains intact even under harsh conditions such as high temperature and spraying. It can provide long-term and stable fire protection for the substrate and can effectively inhibit the release of combustible gases and smoke particles, thereby enhancing its practical application value.

[0018] Boron / silicon compounds, as ceramic precursors, have flame-retardant properties, and titanium dioxide has excellent heat and weather resistance, high chemical stability, and excellent corrosion resistance. Phytic acid is a renewable resource, primarily found in plant seeds, roots, and stems. Because its molecular structure contains six phosphate groups (with a P content of up to 28%), it is an ideal material for constructing efficient and environmentally friendly flame-retardant systems. The present invention, through structural design, employs boron / silicon ceramic precursors and titanium dioxide to synergistically construct composite ceramics. This allows for surface modification of titanium dioxide by the boron / silicon ceramic precursor and phytic acid, enhancing the fire-resistant properties of the fire-retardant coating. This expands the utilization of biomass resources and effectively strengthens the expanded carbon layer of the fire-retardant coating.

[0019] This invention addresses the question of how to improve the char strength and fire resistance of intumescent fire-retardant coatings for steel structures. Based on the traditional "ammonium polyphosphate-pentaerythritol-melamine" intumescent flame-retardant system, this invention utilizes a water-based resin as a film-forming substance and organically modified titanium dioxide containing a boron / silicon ceramic precursor and phytic acid as the building blocks of the intumescent char reinforcement system to develop a high-performance, environmentally friendly fire-retardant coating. Surface modification of the titanium dioxide enhances its interfacial bonding within the coating system and strengthens its compatibility with the resin matrix. The modified titanium dioxide acts as a multifunctional synergist, utilizing phosphorus radicals generated by the thermal decomposition of phytic acid to capture hydroxyl radicals produced during combustion, thereby blocking the combustion chain reaction (gas-phase flame retardancy). Furthermore, the coating expands when exposed to fire. As the temperature rises, the boron / silicon ceramic precursor contributes to the formation of the intumescent ceramic char layer and improves its strength. On the other hand, based on the good thermal stability of titanium dioxide, it reacts with the acid source at high temperature to form high-temperature resistant titanium pyrophosphate (TiP2O7) which is embedded in the matrix, thereby enhancing the structure of the expanded carbon layer (condensed phase flame retardant), which is more conducive to long-term and durable fire-resistant protection of the substrate.

[0020] Compared to existing intumescent flame-retardant systems, the modified titanium dioxide-based intumescent carbon layer-reinforced flame-retardant system provided by the present invention effectively strengthens the intumescent carbon layer without the need for other ceramic fillers. The modified titanium dioxide employed in the present invention can be evenly dispersed throughout the system, and during combustion, the coating forms a dense, continuous phosphorus-boron / silicon-carbon structure embedded with the high-temperature-resistant TiP2O7 component. This increases the amount of carbon residue after ablation, blocks heat transfer, and effectively reduces the release of combustible gases and smoke particles.

[0021] Furthermore, the modified titanium dioxide of the present invention is prepared through a simple process and incorporates phytic acid, a renewable biomass resource. The raw materials used in the intumescent carbon layer-reinforced water-based fire retardant coating of the present invention are environmentally friendly, low-toxic, and low-cost. The production process is consistent with the route of traditional fire retardant coatings, with low energy consumption, ease of commercial production, and industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 FT-IR (a) and XPS (b) spectra of TiO2, BSTi, and PBSTi in Example 1; Figure 2 TG curves of TiO2, BSTi, and PBSTi in Example 1; Figure 3 This is a picture of the dispersion state of TiO2 and PBSTi in Example 1; Figure 4 is the bonding strength of the fire retardant coatings in Examples 1 to 3 and Comparative Examples 1 to 2; Figure 5TG curves of the fire retardant coatings in Examples 1 to 3 and Comparative Examples 1 to 2; Figure 6 The fire resistance curves of the fire retardant coating and the steel plate in Examples 1 to 3 and Comparative Examples 1 to 2; Figure 7 is the expansion ratio of the fire retardant coating in Examples 1 to 3 and Comparative Examples 1 to 2; Figure 8 This is a test diagram of the strength of the expanded carbon layer of the coating obtained in Example 2 and Comparative Example 1 after ablation; Figure 9 The heat release rate (a), total heat release (b), and total smoke generation curve (c) of the coatings obtained in Example 2 and Comparative Example 1 after ablation; Figure 10 The coatings obtained in Example 2 and Comparative Example 1 are in the state of expanded carbon layers after ablation. DETAILED DESCRIPTION

[0023] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.

[0024] The present invention provides an intumescent carbon layer reinforced water-based fire retardant coating, which comprises the following preparation raw materials, based on the total mass fraction of the intumescent carbon layer reinforced water-based fire retardant coating being 100%: Film-forming substance 18~30%, flame retardant 45~60%, modified titanium dioxide 3.5~12%, additive 1~5%, water 13~25%; The preparation method of the modified titanium dioxide comprises the following steps: Mixing titanium dioxide, a first dispersant, a boron compound, a silicon compound, and an amino compound, adjusting the pH value to 3-4, and performing a first modification to obtain boron / silicon modified titanium dioxide; the amino compound is γ-aminopropyltriethoxysilane; The boron / silicon modified titanium dioxide is mixed with a second dispersant and a phytic acid solution to perform a second modification to obtain modified titanium dioxide.

[0025] Taking the total mass fraction of the expanded carbon layer reinforced water-based fire-retardant coating as 100%, the raw materials for preparing the expanded carbon layer reinforced water-based fire-retardant coating provided by the present invention include 18~30% of film-forming substances, preferably 20.4~25%, and further preferably 21.1~21.9%.

[0026] In the present invention, the film-forming material preferably includes at least one of a water-based epoxy resin, a water-based acrylic resin, a water-based polyurethane resin, a water-based silicone resin, and a water-based alkyd resin. When the film-forming material comprises two or more of the aforementioned types, the present invention does not specifically limit the ratio of the different types of film-forming materials; any ratio may be used. The present invention does not specifically limit the specific specifications or sources of the film-forming material; any commercially available product known in the art may be used.

[0027] When the film-forming substance is a water-based epoxy resin, the film-forming substance preferably further comprises a curing agent; the mass ratio of the water-based epoxy resin to the curing agent is preferably 10 to 20:1. The present invention is not particularly limited to the type of curing agent; a commercially available curing agent corresponding to the desired epoxy resin can be used.

[0028] Taking the total mass fraction of the expanded carbon layer reinforced water-based fire-retardant coating as 100%, the raw materials for preparing the expanded carbon layer reinforced water-based fire-retardant coating provided by the present invention include 45~60% flame retardant, more preferably 51.5~55.5%, and further preferably 52.9~53.4%.

[0029] In the present invention, the flame retardant preferably includes ammonium polyphosphate, pentaerythritol and melamine (traditional intumescent flame retardant system); the mass ratio of ammonium polyphosphate, pentaerythritol and melamine is preferably 2.67~3.25:1~1.5:1.25~1.75, more preferably 2.8~3.2:1~1.3:1.28~1.5, and further preferably 3:1:1.3~1.6.

[0030] Taking the total mass fraction of the expanded carbon layer reinforced water-based fire-retardant coating as 100%, the raw materials for preparing the expanded carbon layer reinforced water-based fire-retardant coating provided by the present invention include 3.5~12% modified titanium dioxide, more preferably 3.9~11.5%, and further preferably 7.5~10.9%.

[0031] In the present invention, the preparation method of the modified titanium dioxide comprises the following steps: Mixing titanium dioxide, a first dispersant, a boron compound, a silicon compound, and an amino compound, adjusting the pH value to 3-4, and performing a first modification to obtain boron / silicon modified titanium dioxide; the amino compound is γ-aminopropyltriethoxysilane; The boron / silicon modified titanium dioxide is mixed with a second dispersant and a phytic acid solution to perform a second modification to obtain modified titanium dioxide.

[0032] In the present invention, the boron compound preferably includes one or more of trimethoxyboroxane, boric acid and trimethyl borate; when the boron compound is two or more of the above, the present invention has no special limitation on the ratio of different types of boron compounds, and any ratio is acceptable.

[0033] In the present invention, the silicon compound preferably includes one or more of ethyl orthosilicate, vinyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane and tetramethyl orthosilicate; when the silicon compound is two or more of the above, the present invention has no special limitation on the ratio of different types of silicon compounds, and any ratio is acceptable.

[0034] In the present invention, the mass ratio of the titanium dioxide, boron compound, silicon compound and amino compound is preferably 8-10:1.25-2.5:0.5-1.5:1-3, more preferably 9-10:1.5-2.4:1.0-1.5:2-3, and further preferably 10:2.5:1.5:3.

[0035] The present invention utilizes the electrostatic binding effect between the amino group in the amino compound (γ-aminopropyltriethoxysilane) and the phosphorus hydroxyl group in phytic acid to modify phytic acid onto the surface of titanium dioxide. At the same time, the amino compound also has the function of providing silicon element.

[0036] In the present invention, the first dispersant is preferably an anhydrous ethanol-water mixture; the mass ratio of the anhydrous ethanol to water is preferably 1:2. The present invention has no particular limitation on the amount of the first dispersant, as long as the material is completely dispersed.

[0037] The present invention preferably disperses titanium dioxide in a first dispersant, then adds a boron compound, a silicon compound, and an amino compound, adjusts the pH value of the system to 3-4, more preferably 3.5, and magnetically stirs at room temperature for 3-3.5 hours before performing the first modification.

[0038] The present invention preferably uses a hydrochloric acid solution to adjust the pH value; the present invention has no special limitation on the concentration of the hydrochloric acid solution, and the pH value can be adjusted to the desired value as needed.

[0039] In the present invention, the temperature of the first modification is preferably 60-90 ° C, more preferably 70-85 ° C, and the time is preferably 5-7 h, more preferably 6 h.

[0040] After completing the first modification, the present invention preferably filters and washes the obtained product three times to obtain boron / silicon modified titanium dioxide, which is recorded as BSTi.

[0041] In the present invention, the mass concentration of the phytic acid solution is preferably 70%, and the mass ratio of the boron / silicon modified titanium dioxide to the phytic acid solution is preferably 2.5-5:1, more preferably 2.86-3.4:1.

[0042] In the present invention, the second dispersant is preferably an anhydrous ethanol-water mixture, and the mass ratio of the anhydrous ethanol to water is preferably 1:2.

[0043] In the present invention, the boron / silicon modified titanium dioxide is preferably dispersed in a second dispersant, and a phytic acid solution is added to perform the second modification.

[0044] In the present invention, the temperature of the second modification is preferably 60-90 ° C, more preferably 70-85 ° C, and the time is preferably 3-5 h, more preferably 4 h.

[0045] After completing the second modification, the present invention preferably filters and washes the obtained product three times, and then dries it to obtain phosphorus / boron / silicon modified titanium dioxide, which is recorded as PBSTi.

[0046] The modified titanium dioxide described in the present invention is titanium dioxide modified by boron / silicon ceramic precursor and phytic acid.

[0047] Taking the total mass fraction of the expanded carbon layer reinforced water-based fire retardant coating as 100%, the raw materials for preparing the expanded carbon layer reinforced water-based fire retardant coating provided by the present invention include 1 to 5% of additives, more preferably 2.1 to 2.2%.

[0048] In the present invention, the auxiliary agent preferably includes at least one of a dispersant, a thickener, a wetting agent, a defoaming agent and an antibacterial agent.

[0049] In the present invention, the dispersant preferably comprises sodium polyacrylate; the thickener preferably comprises a polyurethane thickener; the wetting agent preferably comprises a nonionic wetting agent; the defoamer preferably comprises a silicone defoamer; and the antimicrobial agent preferably comprises a kasson antimicrobial agent. The present invention does not particularly limit the specific specifications of the dispersant, thickener, wetting agent, defoamer, and antimicrobial agent; any commercially available products of the aforementioned types known in the art may be used.

[0050] In the present invention, based on the total mass fraction of the expanded carbon layer reinforced water-based fire-retardant coating as 100%, the mass percentage of the dispersant is preferably 0.5~0.65%, more preferably 0.56~0.62%; the mass percentage of the thickener is preferably 0.4~0.6%, more preferably 0.5~0.52%; the mass percentage of the wetting agent is preferably 0.25~0.45%, more preferably 0.33~0.37%; the mass percentage of the defoaming agent is preferably 0.35~0.6%, more preferably 0.44~0.52%; the mass percentage of the antibacterial agent is preferably 0.22~0.35%, more preferably 0.26~0.31%.

[0051] Taking the total mass fraction of the expanded carbon layer reinforced water-based fire-retardant coating as 100%, the raw materials for preparing the expanded carbon layer reinforced water-based fire-retardant coating provided by the present invention include 13~25% water, more preferably 15.1~16.3%, and further preferably 15.7%.

[0052] The present invention provides a method for preparing the expanded carbon layer reinforced water-based fire retardant coating described in the above technical solution, comprising the following steps: The film-forming material is dispersed in water, and a flame retardant, modified titanium dioxide and an auxiliary agent are added to obtain an expanded carbon layer reinforced water-based fire retardant coating.

[0053] The present invention preferably disperses the film-forming material in water (1000 rpm, 5 min), adds the flame retardant and modified titanium dioxide to the resulting dispersion, and adds the additive under stirring conditions (1500 rpm, 30 min) to obtain an expanded carbon layer reinforced water-based fire retardant coating.

[0054] The present invention provides the use of the intumescent carbon layer reinforced water-based fire retardant coating described in the above technical solution, or the intumescent carbon layer reinforced water-based fire retardant coating prepared by the preparation method described in the above technical solution, in a fire retardant coating for steel structures. The present invention does not particularly limit the method of application, and the application can be carried out according to methods well known in the art.

[0055] The specific embodiments of the present invention are described in detail below, but it should be understood that the scope of protection of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0056] The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified; the following reagents and raw materials are commercially available unless otherwise specified.

[0057] Example 1

[0058] This embodiment provides a preparation method for an intumescent carbon layer-reinforced water-based fire retardant coating, comprising the following steps: (1) Preparation of modified titanium dioxide 10 g of titanium dioxide (TiO2, R-930, Langfang Lanke Chemical Co., Ltd.) was dispersed in a mixed solution containing anhydrous ethanol (130 g) and deionized water (260 g). Subsequently, 2.5 g of trimethoxyboron (Shanghai MacLean Biochemical Technology Co., Ltd.), 1.5 g of ethyl orthosilicate (Shanghai MacLean Biochemical Technology Co., Ltd.), and 3 g of γ-aminopropyltriethoxysilane (Shanghai MacLean Biochemical Technology Co., Ltd.) were added. The pH value of the system was adjusted to 3.5 with 20% hydrochloric acid solution. The mixture was magnetically stirred at room temperature for 3 h, then heated to 85 °C and reacted for 6 h. After filtration and washing three times, boron / silicon modified titanium dioxide was obtained, which was designated as BSTi. 10 g of the above-mentioned boron / silicon modified titanium dioxide was dispersed in a mixed solution containing anhydrous ethanol (130 g) and deionized water (260 g). 3.5 g of phytic acid solution (mass concentration of 70%, Shanghai Aladdin Biochemical Technology Co., Ltd.) was added and magnetically stirred at 85 °C for 4 h. The mixture was filtered, washed three times and then dried to obtain phosphorus / boron / silicon modified titanium dioxide, which was recorded as PBSTi.

[0059] (2) Preparation of expanded carbon layer reinforced water-based fire retardant coating

[0060] First, 32 g of waterborne epoxy resin emulsion (ALQ-RE 2156, Tianjin Aoluqi Chemical Technology Co., Ltd.) was dispersed in 25 g of deionized water (1000 rpm, 5 min), and then 48 g of ammonium polyphosphate (Exolit AP422, Clariant Chemical Technology (Shanghai) Co., Ltd.), 16 g of pentaerythritol (Charmor PM40, Perstorp (Shanghai) Chemical Products Trading Co., Ltd.), 21 g of melamine (Mingyue, Shandong Mingyue Chemical Co., Ltd.), and 6 g of modified titanium dioxide prepared in step (1) were added to the above solution, and 1 g of dispersant (SC-860, Aohan Shengchuan Chemical (Beijing) Co., Ltd.), 0.8 g of thickener (UH-752, Aidico (Shanghai) Trading Co., Ltd.), 0.5 g of wetting agent (SC-407, Aohan Shengchuan Chemical (Beijing) Co., Ltd.), 0.8 g of ethanol were added under stirring (1500 rpm, 30 min). g defoamer (BWF-WM906, Jinan Yuanyang Chemical Co., Ltd.), 0.4 g antibacterial agent (SC-189, Aohan Shengchuan Chemical (Beijing) Co., Ltd.), and finally 1.6 g water-based epoxy curing agent (ALQ-354, Tianjin Aoluqi Chemical Technology Co., Ltd.) were added to obtain the expanded carbon layer reinforced water-based fire retardant coating.

[0061] Example 2

[0062] (1) The preparation of modified titanium dioxide is the same as in Example 1.

[0063] (2) The preparation of the expanded carbon layer reinforced water-based fire retardant coating was the same as in Example 1, except that the amount of modified titanium dioxide added in step (1) was 12 g.

[0064] Example 3

[0065] (1) The preparation of modified titanium dioxide is the same as in Example 1.

[0066] (2) The preparation of the expanded carbon layer reinforced water-based fire retardant coating was the same as in Example 1, except that the amount of modified titanium dioxide added in step (1) was 18 g.

[0067] Example 4

[0068] (1) The preparation of modified titanium dioxide is the same as in Example 1.

[0069] (2) The preparation of the expanded carbon layer reinforced water-based fire retardant coating is the same as in Example 1, except that the water-based epoxy resin is replaced by a water-based acrylic resin (FX-9116, Nantong Fangxin Chemical Co., Ltd.), and there is no need to introduce a water-based epoxy curing agent.

[0070] Example 5

[0071] (1) The preparation of modified titanium dioxide is the same as in Example 1.

[0072] (2) The preparation of the expanded carbon layer reinforced water-based fire retardant coating is the same as in Example 1, with the only difference being that the water-based epoxy resin is replaced by a water-based polyurethane resin (SEAPUR 50G33, Guangdong Xidun New Material Technology Co., Ltd.) and a water-based silicone resin (VR2402, Shenzhen Weiteli Environmental Protection Materials Co., Ltd.), wherein the mass ratio of the water-based polyurethane resin to the water-based silicone resin is 1:1, and there is no need to introduce a water-based epoxy curing agent.

[0073] Example 6

[0074] (1) Preparation of modified titanium dioxide

[0075] 10 g of titanium dioxide (R-930, Langfang Lanke Chemical Co., Ltd.) was dispersed in a mixed solution containing anhydrous ethanol (130 g) and deionized water (260 g). Subsequently, 2.4 g of trimethyl borate (Shandong Xinshunli Chemical Technology Co., Ltd.), 1.6 g of tetramethyl orthosilicate (Shandong Rongsheng New Materials Co., Ltd.), and 3 g of γ-aminopropyltriethoxysilane (Shanghai MacLean Biochemical Technology Co., Ltd.) were added. The pH value of the system was adjusted to 4 with 20% hydrochloric acid solution. The mixture was magnetically stirred at room temperature for 3.5 h, then heated to 90 °C and reacted for 5 h. The mixture was filtered and washed three times to obtain boron / silicon modified titanium dioxide. The above-mentioned boron / silicon modified titanium dioxide (12 g) was dispersed in a mixed solution containing anhydrous ethanol (130 g) and deionized water (260 g), and 3.5 g of phytic acid solution (Shanghai Aladdin Biochemical Technology Co., Ltd.) was added. The mixture was magnetically stirred at 85 °C for 4 h. After filtration and washing three times, it was dried to obtain phosphorus / boron / silicon modified titanium dioxide.

[0076] (2) The preparation of the expanded carbon layer reinforced water-based fire retardant coating is the same as in Example 2.

[0077] Example 7

[0078] (1) The preparation of modified titanium dioxide was the same as in Example 6, except that trimethyl borate was replaced by boric acid (Jinan Century Tongda Chemical Co., Ltd.).

[0079] (2) Preparation of expanded carbon layer reinforced water-based fire retardant coating

[0080] First, 35 g of waterborne acrylic resin (FX-9116, Nantong Fangxin Chemical Co., Ltd.) was dispersed in 25 g of deionized water (1000 rpm, 5 min), and then 45 g of ammonium polyphosphate (Exolit AP422, Clariant Chemical Technology (Shanghai) Co., Ltd.), 15 g of pentaerythritol (Charmor PM40, Perstorp (Shanghai) Chemical Products Trading Co., Ltd.), 25 g of melamine (Mingyue, Shandong Mingyue Chemical Co., Ltd.), and 12 g of the modified titanium dioxide prepared in step (1) were added to the above solution, and 0.9 g of dispersant (SC-860, Aohan Shengchuan Chemical (Beijing) Co., Ltd.), 0.8 g of thickener (UH-752, Aidico (Shanghai) Trading Co., Ltd.), 0.6 g of wetting agent (SC-407, Aohan Shengchuan Chemical (Beijing) Co., Ltd.), 0.7 g of defoaming agent (BWF-WM906, Jinan Yuanyang Chemical Co., Ltd.), 0.5 g of ethanol were added under stirring (1500 rpm, 30 min). g antibacterial agent (SC-189, Aohan Shengchuan Chemical (Beijing) Co., Ltd.) to obtain the expanded carbon layer reinforced water-based fire retardant coating.

[0081] Comparative Example 1

[0082] The preparation of the water-based fire retardant coating is the same as that in Example 2, except that neither modified titanium dioxide nor titanium dioxide is added to the system.

[0083] Comparative Example 2

[0084] The preparation of the water-based fire retardant coating was the same as in Example 2, except that the modified titanium dioxide was replaced by unmodified titanium dioxide raw material, and the added amount was 12 g.

[0085] Structural characterization

[0086] 1) FT-IR and XPS were used to characterize the chemical structure of titanium dioxide before and after modification in Example 1. The results are as follows: Figure 1 shown.

[0087] Figure 1 FT-IR (a) and XPS (b) spectra of TiO2, BSTi and PBSTi in Example 1; Figure 1 As can be seen in (a), the FT-IR spectrum of boron / silicon modified titanium dioxide (BSTi) is at 2946 cm -1 , 1520 cm -1and 800 cm -1 The stretching vibration peaks of CH, NH and Si-C in γ-aminopropyltriethoxysilane appeared at 920 cm-1, indicating that γ-aminopropyltriethoxysilane has been successfully grafted onto the titanium dioxide surface. -1 The absorption peak corresponding to Si-OB is at 3406 cm, indicating that the B element has also been modified on the titanium dioxide surface. -1 The stretching vibration peak at 1520 cm- -1 The bending vibration absorption peak at NH is weakened, indicating that the hydroxyl group in phytic acid and the amino group in γ-aminopropyltriethoxysilane form an ionic bond through electrostatic bonding. From the XPS spectrum of BSTi ( Figure 1 As can be seen in (b), compared to unmodified titanium dioxide, new peaks at 192.1 eV and 401.8 eV attributed to the elements B and N appear due to the introduction of trimethoxyboroxy ester and γ-aminopropyltriethoxysilane. In addition, the XPS spectrum of PBSTi is almost identical to that of BSTi, except for the appearance of a new peak at 133.5 eV attributed to the element P, indicating that phytic acid has been successfully modified on the titanium dioxide surface.

[0088] 2) The thermal stability of titanium dioxide before and after modification in Example 1 was characterized by TG. The thermogravimetric curves are as follows: Figure 2 shown. Figure 2 is the TG curve of TiO2, BSTi and PBSTi in Example 1; Figure 2 As shown, the unmodified titanium dioxide exhibited almost no weight loss within the test range, demonstrating good thermal stability of the inorganic material. After the introduction of trimethoxyboron ester, ethyl orthosilicate, and γ-aminopropyltriethoxysilane, the BSTi sample exhibited some thermal weight loss, with a mass loss rate of approximately 5.5% after heating at 800°C, which can be mainly attributed to the thermal degradation of the organic components. Further introduction of phytic acid increased the thermal weight loss rate of the PBSTi sample to 6.1%, but it remained at a low level, primarily due to the inorganic components. These results further demonstrate the successful preparation of the phosphorus / boron / silicon modified titanium dioxide sample.

[0089] 3) The titanium dioxide (TiO2, PBSTi) before and after modification in Example 1 was dispersed in deionized water by ultrasound (100 W, 20 min), and the dispersion state was observed using a metallographic polarizing microscope (WMJ-9590, Shanghai Precious Instrument Co., Ltd.). Figure 3As shown in the figure, after ultrasonic dispersion, TiO2 showed obvious agglomeration in deionized water. Under the same conditions, the organically modified PBSTi sample showed a better dispersion state and the agglomeration phenomenon was significantly improved, providing a good basis for the further preparation of expanded carbon layer reinforced water-based fire retardant coatings.

[0090] Performance Testing

[0091] 1) The bond strength of water-based fire retardant coatings was tested in accordance with GB 14907-2018. The bond strength between the expanded carbon layer reinforced water-based fire retardant coating and the steel plate was evaluated by a pull-out test.

[0092] Figure 4 is the bonding strength of the fire retardant coatings in Examples 1 to 3 and Comparative Examples 1 to 2; Figure 4 As shown, the bond strength of Comparative Example 1 is 0.58 MPa, while as the amount of modified titanium dioxide introduced into the system gradually increases, the bond strengths of Examples 1, 2, and 3 decrease to 0.56 MPa, 0.46 MPa, and 0.38 MPa, respectively. This is primarily because the increased amount of inorganic nanoparticles reduces the system's cohesive force, affecting the bonding performance between the resin matrix and the substrate. Notably, compared to Example 2, the bond strength of the fire-retardant coating (Comparative Example 2) containing the same amount of unmodified titanium dioxide decreases to 0.35 MPa. This can be attributed to the improved dispersibility of the modified titanium dioxide in the resin matrix, while the unmodified titanium dioxide partially agglomerates in the resin matrix, affecting its film-forming continuity and resulting in a decrease in bond strength.

[0093] 2) Thermogravimetric analysis of waterborne fire retardant coatings: STA 449F5 thermal analyzer, heating rate of 20 °C / min, temperature range of 40-800 °C, nitrogen atmosphere.

[0094] Figure 5 TG curves of the fire retardant coatings in Examples 1 to 3 and Comparative Examples 1 to 2; Figure 5The TG curve of the fire-retardant coating under a nitrogen atmosphere shows that with increasing amounts of modified titanium dioxide incorporated into the system, the thermal stability of the fire-retardant coating gradually increases, and the residual carbon content also significantly improves. The fire-retardant coating prepared in this invention is based on the traditional "ammonium polyphosphate-pentaerythritol-melamine" intumescent flame retardant system, and its thermal decomposition process is relatively similar. As the coating is gradually heated, the water in the system gradually evaporates, and small molecules decompose. As the temperature rises further, the intumescent carbon layer is formed due to the thermal degradation of ammonium polyphosphate to produce acid, the melt dehydration and carbonization and crosslinking of pentaerythritol, and the decomposition of melamine to produce gas. The temperature range of 510-800°C is attributed to the further decomposition of the intumescent carbon layer at high temperatures, with relatively little mass loss. The introduction of organically modified titanium dioxide facilitates the formation of a higher-quality intumescent carbon layer in this stage, creating a good synergistic effect with the "PCN" intumescent flame retardant system. The mass residual rates of Examples 1, 2, and 3 were 43.5%, 47.6%, and 52.8%, respectively, significantly higher than the 30.5% mass residual rate of Comparative Example 1. A higher carbon residue is beneficial for improving the fire resistance of intumescent fire retardant coatings. Notably, the mass residual rate of the fire retardant coating (Comparative Example 2) containing the same amount of unmodified titanium dioxide was slightly higher at 48.5% compared to Example 2. This is primarily due to the fact that the modified titanium dioxide, coated with organic components (silicon compounds, γ-aminopropyltriethoxysilane, and phytic acid), undergoes cracking after high-temperature ablation, resulting in increased overall heat loss from the fire retardant coating system.

[0095] 3) Fire resistance test: First, apply the expanded carbon layer reinforced water-based fire retardant coating to the surface of the steel plate (coating thickness: 1.5 mm). After it is completely dry, fix it on the iron frame and burn it with a methane torch. The distance between the flame and the steel plate is 8.5 cm. A K-type thermocouple is bonded to the back of the steel plate. The back temperature is monitored in real time using a data logger. The results are shown in the figure. Figure 6 .

[0096] Figure 6 The fire resistance curves of the fire retardant coating and the steel plate in Examples 1 to 3 and Comparative Examples 1 to 2 are shown; Figure 6As can be seen from the data, the back temperature of the steel plate uncoated with fire retardant coating reached 510°C after continuous methane spraying for 20 minutes. However, the back temperatures of the steel plates coated with the fire retardant coatings from Comparative Example 1, Examples 1, 2, and 3 reached 256.5°C, 262.7°C, 266.9°C, and 299.8°C, respectively, at the same spraying time. It can be seen that the thermal insulation performance of the fire retardant coating decreases slightly with increasing the amount of modified titanium dioxide in the system. This is primarily because the introduction of inorganic fillers increases the foaming viscosity of the expansion system, suppressing the expansion ratio of the coating and thus affecting the thermal insulation performance. Compared with Comparative Example 2 in which the same amount of unmodified titanium dioxide is added (back temperature 271.9°C), the steel plate coated with Example 2 has a lower back temperature. The reason may be that the surface of the modified titanium dioxide is modified with flame retardant elements such as P, B, and Si. After high-temperature calcination, it can jointly construct a high-quality carbon layer (forming a ceramic body) with the intumescent flame retardant system and refractory fillers, thereby improving the fire resistant and heat-insulating properties of the coating.

[0097] 4) Use a ruler to measure the expansion height of the fire retardant coating after methane spray gun ablation, and calculate the expansion ratio based on the ratio of the expanded height to the initial coating thickness (1.5 mm). For example, if the initial coating thickness is 1.5 mm and the thickness expanded after ablation is A, then the expansion ratio is A / 1.5 100%.

[0098] Figure 7 is the expansion ratio of the fire retardant coating in Examples 1 to 3 and Comparative Examples 1 to 2; Figure 7 It can be seen that the change trend of the expansion ratio of the prepared intumescent carbon layer reinforced water-based fire retardant coating is consistent with the combustion background temperature test results. With the increase of the amount of modified titanium dioxide introduced, the expansion ratio is reduced from 24.3% in Comparative Example 1 to 17.6% in Example 3. This is because the coating generates a dense phosphorus-silicon / boron-carbon structure during the combustion process, and high-temperature resistant components such as titanium pyrophosphate are embedded in it. The excessive proportion of inorganic fillers in the system will limit the expansion of the non-combustible gas to the carbon layer, resulting in a decrease in the expansion ratio, but still showing good fireproofing and heat insulation properties. It is worth noting that compared with Comparative Example 2, the expansion ratio of Example 2 is slightly higher, which may be due to the high dispersibility of the modified titanium dioxide and the thermal decomposition of the organic components on its surface (such as silicon compounds, γ-aminopropyltriethoxysilane, phytic acid) to produce gas, which to a certain extent improves the expansion capacity of the carbon layer.

[0099] 5) Place a 100 g weight vertically on the surface of the expanded carbon layer of the fire retardant coating after methane torch ablation during the fire resistance test in 3) above, and observe whether the expanded carbon layer can withstand the weight of the weight.

[0100] Figure 8The graph showing the strength of the expanded carbon layer after ablation of the coatings obtained in Example 2 and Comparative Example 1 (thickness 1.5 mm) is shown; Figure 8 The results show that the expanded carbon layer of the coating obtained in Example 2 after ablation has high strength and can withstand a 100g weight without collapsing or breaking. However, the expanded carbon layer of the coating obtained in Comparative Example 1 cannot withstand this weight, and the weight sinks into the expanded carbon layer. This further demonstrates that the introduction of modified titanium dioxide can significantly improve the strength of the expanded carbon layer of the fire-retardant coating, which is beneficial for better protecting the substrate material in actual fire scenarios. In summary, although the bond strength and expansion ratio of Comparative Example 1 are relatively high, its expanded carbon layer is very weak and easily breaks after heat flow and external impact, thus losing its fire protection ability.

[0101] 6) The combustion behavior of fire retardant coating (100 mm × 100 mm × 0.6 mm) was analyzed using FTT cone calorimeter according to ISO 5660-1, with a thermal radiation power of 35 kW / m 2 .

[0102] Figure 9 The heat release rate (a), total heat release (b) and total smoke generation curve (c) of the fire retardant coating obtained in Example 2 and Comparative Example 1 after ablation. Figure 9 It can be seen that the heat release rate of the coating obtained in Comparative Example 1 reaches a peak of 103.5 kW / m at 47 s. 2 , while the heat release rate of the coating obtained in Example 2 reached a peak of 89.6 kW / m at 56 s. 2 , indicating that modified titanium dioxide can play a better fire protection role in fire retardant coatings. In addition, the total heat release and total smoke generation of the coating obtained in Comparative Example 1 were 4.3 MJ / m 2 and 0.28 m 2 , while the total heat release and total smoke generation of the coating obtained in Example 2 were reduced to 3.6 MJ / m 2 and 0.25 m 2 This can be mainly attributed to the fact that the introduction of modified titanium dioxide into the intumescent flame retardant system can generate a denser and continuous intumescent carbon layer during the combustion process, which hinders heat transfer and effectively reduces the release of combustible gases and smoke particles.

[0103] 7) Scanning electron microscopy (SEM) was used to study the microscopic morphology of the residual carbon after ablation of the expanded carbon layer reinforced water-based fire retardant coating.

[0104] Figure 10 The coatings obtained in Example 2 and Comparative Example 1 are in the state of expanded carbon layer after ablation; Figure 10As can be seen from the results, the expanded carbon layer of the coating obtained in Example 2 after ablation is loose, with an incomplete surface and large pores. In contrast, the expanded carbon layer structure of the coating obtained in Comparative Example 1 after ablation exhibits good continuity and integrity, with no obvious pores and a dense surface, which can serve as an excellent barrier to heat and smoke transmission. This is mainly due to the participation of inorganic fillers containing ceramic precursors in the formation of the carbon layer skeleton, and the high titanium phosphate formed by the complete combustion of titanium dioxide and ammonium polyphosphate or its degradation products is embedded in the matrix, which strengthens the expanded carbon layer structure and is more conducive to long-term and durable fire-resistant protection of the substrate.

[0105] For Examples 4 and 5, after replacing the film-forming substance, the bonding strength, expansion ratio and fire resistance of the obtained intumescent fire-retardant coating did not change significantly compared with Example 1. The bonding strength of Example 4 was 0.55 MPa, the expansion ratio was 23%, and the back temperature after the 20-min fire resistance test was 261.5°C; the bonding strength of Example 5 was 0.51 MPa, the expansion ratio was 21.5%, and the back temperature after the 20-min fire resistance test was 259.6°C, indicating that the choice of film-forming substance has relatively little effect on the performance of the fire-retardant coating.

[0106] The intumescent fire-retardant coating obtained in Example 6 exhibited a bond strength of 0.48 MPa, an expansion ratio of 20.2%, and a back temperature of 269.7°C after a 20-minute fire test. Compared to Example 2, the intumescent fire-retardant coating obtained in Example 7 exhibited a bond strength of 0.46 MPa, an expansion ratio of 26.2%, and a back temperature of 253.5°C after a 20-minute fire test. This was primarily due to the increased amount of melamine (gas source) introduced in Example 7, which generated more gas after ablation of the coating, increasing the system's expansion ratio and thus improving fire resistance.

[0107] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. An expanded carbon layer reinforced water-based fire retardant coating, characterized in that: Taking the total mass fraction of the expanded carbon layer reinforced water-based fire retardant coating as 100%, the coating includes the following preparation raw materials: Film-forming substance 18~30%, flame retardant 45~60%, modified titanium dioxide 3.5~12%, additive 1~5%, water 13~25%; The preparation method of the modified titanium dioxide comprises the following steps: Mixing titanium dioxide, a first dispersant, a boron compound, a silicon compound, and an amino compound, adjusting the pH value to 3-4, and performing a first modification to obtain boron / silicon modified titanium dioxide; the amino compound is γ-aminopropyltriethoxysilane; The boron / silicon modified titanium dioxide is mixed with a second dispersant and a phytic acid solution to perform a second modification to obtain modified titanium dioxide.

2. The expanded carbon layer reinforced water-based fire retardant coating according to claim 1, characterized in that: The boron compound includes one or more of trimethoxyboryl, boric acid and trimethyl borate; The silicon compound includes one or more of ethyl orthosilicate, vinyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane and tetramethyl orthosilicate; The mass ratio of the titanium dioxide, the boron compound, the silicon compound and the amino compound is 8-10:1.25-2.5:0.5-1.5:1-3; The temperature of the first modification is 60-90 ° C, and the time is 5-7 h.

3. The expanded carbon layer reinforced water-based fire retardant coating according to claim 1, characterized in that: The mass ratio of the boron / silicon modified titanium dioxide to the phytic acid solution is 2.5-5:1; The mass concentration of the phytic acid solution is 70%; The temperature of the second modification is 60-90 ° C, and the time is 3-5 h.

4. The expanded carbon layer reinforced water-based fire retardant coating according to claim 1, characterized in that: The film-forming substance includes at least one of a water-based epoxy resin, a water-based acrylic resin, a water-based polyurethane resin, a water-based silicone resin, and a water-based alkyd resin.

5. The expanded carbon layer reinforced water-based fire retardant coating according to claim 4, characterized in that: When the film-forming substance is a water-based epoxy resin, the film-forming substance further comprises a curing agent; the mass ratio of the water-based epoxy resin to the curing agent is 10-20:

1.

6. The expanded carbon layer reinforced water-based fire retardant coating according to claim 1, characterized in that: The flame retardant comprises ammonium polyphosphate, pentaerythritol and melamine; the mass ratio of the ammonium polyphosphate, pentaerythritol and melamine is 2.67-3.25:1-1.5:1.25-1.

75.

7. The expanded carbon layer reinforced water-based fire retardant coating according to claim 1, characterized in that: The auxiliary agent includes at least one of a dispersant, a thickener, a wetting agent, a defoaming agent and an antibacterial agent.

8. The expanded carbon layer reinforced water-based fire retardant coating according to claim 7, characterized in that: The dispersant includes sodium polyacrylate; the thickener includes a polyurethane thickener; the wetting agent includes a non-ionic wetting agent; the defoaming agent includes an organic silicon defoaming agent; and the antibacterial agent includes a Kathon antibacterial agent.

9. The method for preparing the expanded carbon layer reinforced water-based fire retardant coating according to any one of claims 1 to 8, characterized in that: The following steps are involved: The film-forming material is dispersed in water, and a flame retardant, modified titanium dioxide and an auxiliary agent are added to obtain an expanded carbon layer reinforced water-based fire retardant coating.

10. Use of the intumescent carbon layer reinforced water-based fire retardant coating according to any one of claims 1 to 8 or the intumescent carbon layer reinforced water-based fire retardant coating prepared by the preparation method according to claim 9 in fire retardant coatings for steel structures.

Citation Information

Patent Citations

  • Ultrathin water-based epoxy resin expandable fireproof paint and preparation method thereof

    CN101712840A

  • Water-based intumescent fire retardant coating for indoor steel structure and preparation method thereof

    CN112980262A

  • Flame-retardant heat-insulating composite material and preparation method thereof

    CN116786389A

  • High-carbon-layer-strength intumescent steel structure fireproof coating and preparation method thereof

    CN119931433A

Cited By

  • Composite flame-retardant synergist with core-shell structure, preparation method and application of composite flame-retardant synergist, intumescent fire retardant coating, preparation of intumescent fire retardant coating and application of intumescent fire retardant coating

    CN121991546A